Dual Metabolic Defects Are Required to Produce Hypertriglyceridemia in Obese Subjects - Taskinen, Marja-Riitta; Adiels, Martin; Westerbacka, Jukka; Söderlund, Sanni; Kahri, Juhani; Lundbom, Nina; Lundbom, Jesper; Hakkarainen, Antti; Olofsson, Sven-Olof; Orho-Melander, Marju; Borén, Jan (Arteriosclerosis, thrombosis, and vascular biology, 2011)
OBJECTIVE—Obesity increases the risk of cardiovascular disease and premature death. However, not all obese subjects develop the metabolic abnormalities associated with obesity. The aim of this study was to clarify the mechanisms that induce dyslipidemia in obese subjects. METHODS AND RESULTS—Stable isotope tracers were used to elucidate the pathophysiology of the dyslipidemia in hypertriglyceridemic (n=14) and normotriglyceridemic (n=14) obese men (with comparable body mass index and visceral fat volume) and in normotriglyceridemic nonobese men (n=10). Liver fat was determined using proton magnetic resonance spectroscopy, and subcutaneous abdominal and visceral fat were measured by magnetic resonance imaging. Serum triglycerides in obese subjects were increased by the combination of increased secretion and severely impaired clearance of triglyceride-rich very-low-density lipoprotein1 particles. Furthermore, increased liver and subcutaneous abdominal fat were linked to increased secretion of very-low-density lipoprotein 1 particles, whereas increased plasma levels of apolipoprotein C-III were associated with impaired clearance in obese hypertriglyceridemic subjects. CONCLUSION—Dual metabolic defects are required to produce hypertriglyceridemia in obese subjects with similar levels of visceral adiposity. The results emphasize the clinical importance of assessing hypertriglyceridemic waist in obese subjects to identify subjects at high cardiometabolic risk.